The Effect of Brand Image, Promotion Effectiveness, and Product Quality on Consumer Buying Interest - Aileen Patricia Budi; Zeplin Jiwa Husada Tarigan (Universitas Kristen Petra dan Ikatan Sarjana Ekonomi Indonesia Cabang Surabaya, 2025)
This study aims to analyze the influence of brand image, promotional effectiveness, and product quality on consumer interest in purchasing textbooks from a printing company in Indonesia. The study's background is the increasing competition in the printing industry, which requires companies to strengthen their marketing strategies by improving brand image, effective promotion, and superior product quality. This study uses a quantitative, descriptive approach. Primary data were obtained by distributing questionnaires to 100 respondents who are consumers of printing company products. Data analysis was conducted using SPSS to test the influence of independent variables on the dependent variable via multiple linear regression. The results show that the three independent variables, namely brand image, promotional effectiveness, and product quality, have a positive and significant effect on consumer purchasing interest. Among the three, product quality has the most significant influence on purchasing interest, indicating that consumer perceptions of product quality are a significant factor in purchasing decisions. These findings emphasize the importance for printing companies to continue to maintain product quality, strengthen brand image, and implement effective promotional strategies to increase consumer purchasing interest and expand market share.